Apolipoprotein E (APOE) genotype, dementia, and memory performance among Caribbean Hispanic versus US populations. Issue 2 (4th June 2022) - Llibre‐Guerra, Jorge J.; Li, Jing; Qian, Yuting; Llibre‐Rodriguez, Juan de Jesús; Jiménez‐Velázquez, Ivonne Z.; Acosta, Daisy; Salas, Aquiles; Llibre‐Guerra, Juan Carlos; Valvuerdi, Adolfo; Harrati, Amal; Weiss, Jordan; Liu, Mao‐Mei; et al.
Abstract: Introduction: Apolipoprotein E ( APOE ) is considered the major susceptibility gene for developing Alzheimer's disease. However, the strength of this risk factor is not well established across diverse Hispanic populations. Methods: We investigated the associations among APOE genotype, dementia prevalence, and memory performance (immediate and delayed recall scores) in Caribbean Hispanics (CH), African Americans (AA), Hispanic Americans (HA) and non‐Hispanic White Americans (NHW). Multivariable logistic regressions and negative binomial regressions were used to examine these associations by subsample. Results: Our final dataset included 13, 516 participants (5198 men, 8318 women) across all subsamples, with a mean age of 74.8 years. Prevalence of APOE ε4 allele was similar in CHs, HAs, and NHWs (21.8%–25.4%), but was substantially higher in AAs (33.6%; P  < 0.001). APOE ε4 carriers had higher dementia prevalence across all groups. Discussion: APOE ε4 was similarly associated with increased relative risk of dementia and lower memory performance in all subsamples.